Intention to Consume Alcohol among Dayak Adolescents in Sarawak: An Application of Theory of Planned Behavior - Gahamat, Mohd Faiz; Rahman, Md Mizanur; Safii, Razitasham; Daud, Muhammad Siddiq; Ajeng, Rudy Ngau (Faculty of Medicine Universitas Padjadjaran, 2023)
Objectives: To explore the application of a model that integrates various factors that influence Dayak adolescents' intentions to consume alcohol in Sarawak, Malaysia.Methods: A cross-sectional quantitative study was conducted from September 2019 to February 2022. Through multistage stratified cluster sampling, 12 districts were selected from 12 divisions. Respondents were selected randomly and were interviewed using a questionnaire.Results: Structural equation modeling was used to test the Theory of Planned Behavior (TPB) and explore the relationship between various variables and respondents' intention to consume alcohol. The findings suggest that attitude (β=.22, p<.001), subjective norm (β = .33, p < .001), and perceived behavior control (β =−.41, p<.001) influenced the intention to consume alcohol. In contrast, alcohol consumption was associated with intention (β=.15, p < .001), attitude (β=.20, p<.001), and perceived behavior control (β=−.32, p<.001).Conclusion: The findings demonstrated that the TPB model can be used to explore various variables that influence the intention to consume alcohol among Dayak adolescents, with attitude, subjective norm, and perceived behavior control as the variable influencing the intention. This highlights the need for paying attention to those variables when developing age-appropriate strategies that address various social levels to curb alcohol consumption. Given the concerning rates of risky drinking and dependency, school-based health initiatives and focused screening for Dayak adolescents are crucial.